2019
DOI: 10.1016/j.jped.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and physical fitness in Brazilian adolescents

Abstract: Relationships between the body mass index and physical fitness were generally nonlinear (parabolic) in youth 10-17 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
27
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 22 publications
7
27
2
6
Order By: Relevance
“…Ergenlik döneminde "büyüme sıçramaları" olarak adlandırılan vücudun özellikle kol ve bacaklarda hızlı gelişmeler gözlenebileceği ve buna ek olarak, boy artışı ve büyüme oranlarının en üst düzeyde olması grupların kendi içlerinde antropometrik özellikleri pozitif yönde tetiklemiş olabilir. 30,31 Ayrıca saha büyüklüğü, oyuncu sayısı, çalışma süresi, içeriği ve biçimi gibi faktörler fizik-sel özellikleri önemli ölçüde değiştirebilmekte ve çok sayıda çalışma antropometrik değerlerin futbol performansında önemli faktörler olduğunu göstermektedir. 2,32 Bu durumlar, antropometrik özelliklerin kendi aralarındaki pozitif yönlü ve yüksek düzeyde ilişkili olmasını açıklayabilmektedir.…”
Section: Discussionunclassified
“…Ergenlik döneminde "büyüme sıçramaları" olarak adlandırılan vücudun özellikle kol ve bacaklarda hızlı gelişmeler gözlenebileceği ve buna ek olarak, boy artışı ve büyüme oranlarının en üst düzeyde olması grupların kendi içlerinde antropometrik özellikleri pozitif yönde tetiklemiş olabilir. 30,31 Ayrıca saha büyüklüğü, oyuncu sayısı, çalışma süresi, içeriği ve biçimi gibi faktörler fizik-sel özellikleri önemli ölçüde değiştirebilmekte ve çok sayıda çalışma antropometrik değerlerin futbol performansında önemli faktörler olduğunu göstermektedir. 2,32 Bu durumlar, antropometrik özelliklerin kendi aralarındaki pozitif yönlü ve yüksek düzeyde ilişkili olmasını açıklayabilmektedir.…”
Section: Discussionunclassified
“…In addition, these differences in weight status are frequently observed in adolescence (Morrison et al, 2018). Therefore, rapid developments in the body limbs (arms and legs) called "growth spurts" are observed during adolescence (Akçan et al, 1999) and in addition, the fact that the height increase and growth rates are at the highest level (Lopes et al, 2018) suggested that the weights between the groups may be different. The extra body weight in childhood and adolescence is associated with life-long negative health outcomes (Pavlovic et al, 2018) and adolescents with high weight and body fat, regardless of gender, are also known to have lower motor performance (Barbosa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The BMI is an indicator of the state of weight ranging from extreme weakness to obesity, and also it is a concept that is easily understood by the public (Lopes et al, 2018). At the same time, it is assumed that boys with high BMI will have lower performance in physical fitness tests than children with weak and normal BMI (Lopes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations